2022
DOI: 10.2478/raon-2022-0032
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for melanoma brain metastases: a systematic review

Abstract: Background Radiation therapy (RT) for melanoma brain metastases, delivered either as whole brain radiation therapy (WBRT) or as stereotactic radiosurgery (SRS), is an established component of treatment for this condition. However, evidence allowing comparison of the outcomes, advantages and disadvantages of the two RT modalities is scant, with very few randomised controlled trials having been conducted. This has led to considerable uncertainty and inconsistent guideline recommendations. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 137 publications
(67 reference statements)
1
2
0
Order By: Relevance
“… 22 According to Thompson et al, their systematic review found a difference of 6 months in survival in patients treated only with surgery versus those treated with radiotherapy alone (10 months versus four months, respectively). 23 Like our findings, the median survival in patients treated with radiotherapy alone was five months, and for patients treated with surgery, it was 13 months for metastatic lesions to the CNS.…”
Section: Discussionsupporting
confidence: 83%
“… 22 According to Thompson et al, their systematic review found a difference of 6 months in survival in patients treated only with surgery versus those treated with radiotherapy alone (10 months versus four months, respectively). 23 Like our findings, the median survival in patients treated with radiotherapy alone was five months, and for patients treated with surgery, it was 13 months for metastatic lesions to the CNS.…”
Section: Discussionsupporting
confidence: 83%
“…A recent systematic review analyzed the results of 112 studies that had reported outcomes for patients with MBMs treated with various RT regimens. 26 Although data were mainly derived from nonrandomized studies, limited within-study comparisons showed a trend toward better survival in patients treated with SRS alone (7.5 months) compared with those receiving WBRT alone (3.5 months). This difference may, in part, be attributed to selection biases, as patients with fewer brain lesions and better performance status are more likely to undergo SRS, and these characteristics are associated with more favorable survival outcomes.…”
Section: Local Therapy Modalities In Melanoma Brain Metastasesmentioning
confidence: 99%
“…The findings from this study indicated less cognitive decline among patients who received SRS alone. A recent systematic review analyzed the results of 112 studies that had reported outcomes for patients with MBMs treated with various RT regimens 26 . Although data were mainly derived from nonrandomized studies, limited within-study comparisons showed a trend toward better survival in patients treated with SRS alone (7.5 months) compared with those receiving WBRT alone (3.5 months).…”
Section: Local Therapy Modalities In Melanoma Brain Metastasesmentioning
confidence: 99%
“…Thompson JF et al, in a systematic review performed in 2022, revealed that from the time of diagnosis of brain metastasis, the median survival after SRS alone was 7.5 months [18].…”
Section: Stereotactic Radiosurgery and Whole-brain Radiation Therapymentioning
confidence: 99%